Ethnoveterinary Medicine and Ethnopharmacology in the Main Transhumance Areas of Castilla-La Mancha (Spain) - Rivera, Diego; Verde, Alonso; Fajardo Rodríguez, José; Ríos, Segundo; Alcaraz, Francisco; Cárceles, Carlos; Ortíz, Juana; Valdés, Arturo; Ruíz-Gallardo, Jose Reyes; García-Flores, Aida; Palazón, José Antonio; Obón, Concepción (Frontiers in Veterinary Science, 2022)
In this study, we document the practices of ethnoveterinary medicine and ethnopharmacology in the context of traditional transhumance routes that cross Castilla La Mancha from north to south. Transhumance is a type of grazing system that allows advantage to be taken of winter pastures (wintering places) and summer pastures by seasonal movement, twice a year, of cattle and their shepherds. Our study is based on over 200 interviews (from 1994 to 2021) conducted in 86 localities along eight major transhumance routes “cañadas reales” and 25 other minor transhumance routes, and involved 210 informants, 89 single and 121 groups, and 562 individuals, of which the majority were men. Sixty-three recorded pathologies and their treatments are discussed. Two hundred and two species and substances, belonging to 92 different families, have been recorded from the interviews, of which most are plants. Amid the toxic plant species, the most cited in the interviews are Erophaca baetica (L.) Boiss., Lupinus angustifolius L., and Oenanthe crocata L. Some of the species reported as toxic were reservoirs of pathogens or markers for dangerous areas. One of the fields most widely covered in our study is that of prevention, protection, and control of endo- and ectoparasites. This control is carried out mainly by means of aromatic plants. As a polyvalent species, Daphne gnidium L. is outstanding, and it contributes one-tenth of the records of our study. Among the species of fundamentally therapeutic use, Cistus ladanifer L. stands out by far. Principal Coordinate Analysis (PCoA) based on the repertories of ingredients, separates the routes whose most important sections run through siliceous terrain with its characteristic flora, especially in the provinces of Ciudad Real and Toledo, from the routes that run through the limestone terrain of Albacete and Cuenca, and link the Eastern Mancha and the “Serranía de Cuenca” with Andalusia and the Spanish Levant.